The effect of game environments and students’ computer literacy perceptions on their learning of multimedia design principles and learning environment selection - Ak, Oğuz. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2013., 2013)
Although games are typically thought of as a good potential medium for learning, their effectiveness in educational settings has been largely insufficiently studied. This study was conducted on the Faculty of Education students' learning of the “Principles of Multimedia Design” learning unit in 3 separate learning environments which were traditional, 2D and 3D game-based learning environments to test their effectiveness. The main purposes of this study include: investigating the effect of students' computer literacy perceptions on their achievement and learning environment selection scores in the three environments, identifying effectiveness of environments in students' learning gain, and finding the most suitable environment(s) in terms of learning gains and student preferences. To test these research questions an experimental research design was used. Sixty students were divided into 3 groups , The traditional learning group study the content as 20 students in traditional learning environment, 2D learning group study it as 21 students in 2D game learning environment, and in the 3D game study it as 19 students in 3D game learning environment. As a result of the study it was determined that computer literacy perception does not have any relation with students learning gain or their learning environment selection scores. Moreover, it was determined that all groups made significant learning gains, but none of the learning environments resulted in greater learning gains than the others. Finally the students’ preferred learning environment is determined as 2D games learning environment.
Keywords: Educational games.; Simulation games in education.